2019
DOI: 10.1155/2019/8576961
|View full text |Cite|
|
Sign up to set email alerts
|

Oleuropein-Induced Apoptosis Is Mediated by Mitochondrial Glyoxalase 2 in NSCLC A549 Cells: A Mechanistic Inside and a Possible Novel Nonenzymatic Role for an Ancient Enzyme

Abstract: Oleuropein (OP) is a bioactive compound derived from plants of the genus Oleaceae exhibiting antitumor properties in several human cancers, including non-small-cell lung cancer (NSCLC). Recent evidence suggests that OP has proapoptotic effects on NSCLC cells via the mitochondrial apoptotic pathway. However, the exact molecular mechanisms behind the apoptogenic action of OP in NSCLC are still largely unknown. Glyoxalase 2 (Glo2) is an ancient enzyme belonging to the glyoxalase system involved in the detoxificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 46 publications
1
38
0
Order By: Relevance
“…Moreover, oleuropein induced apoptosis and inhibited the cell proliferation of HepG2 human hepatoma cell line [ 32 ]. More recently, the pro-apoptotic properties of oleuropein were also confirmed by Antognelli et al, who demonstrated that oleuropein induces apoptosis in a non-small cell lung cancer cell line (A549) through the upregulation of mitochondrial glyoxalase 2 [ 33 ]. Anti-tumor effects were also reported for hydroxytyrosol (HT), who reduced the proliferation of human colon adenocarcinoma cells through the inhibition of extracellular signal-regulated kinases (ERK) 1/2 and cyclin D1 [ 34 ].…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, oleuropein induced apoptosis and inhibited the cell proliferation of HepG2 human hepatoma cell line [ 32 ]. More recently, the pro-apoptotic properties of oleuropein were also confirmed by Antognelli et al, who demonstrated that oleuropein induces apoptosis in a non-small cell lung cancer cell line (A549) through the upregulation of mitochondrial glyoxalase 2 [ 33 ]. Anti-tumor effects were also reported for hydroxytyrosol (HT), who reduced the proliferation of human colon adenocarcinoma cells through the inhibition of extracellular signal-regulated kinases (ERK) 1/2 and cyclin D1 [ 34 ].…”
Section: Discussionmentioning
confidence: 88%
“…Human bronchial (BEAS-2B) and alveolar (A549) epithelial cells were obtained from Merck Spa (Milan, Italy). Cells were cultured at the appropriate number in RPMI-1640 (Thermo Fisher Scientific, Monza, Italy), supplemented with 10% heat-inactivated fetal bovine serum (FBS, Thermo Fisher Scientific, Monza, Italy) and 1% antibiotics (penicillin-streptomycin) (Thermo Fisher Scientific, Monza, Italy), at 37 °C in a humidified incubator with 5% CO 2 [ 29 ]. The confluent cells were treated with AuNPs at the final concentrations of 0.8 and 1.6 µg/cm 2 for 3, 24, and 48 h. These concentrations at the indicated time-points were non-toxic or sub-toxic in preliminary experiments (dose-response curves).…”
Section: Methodsmentioning
confidence: 99%
“…Antognelli et al suggested a pro-apoptotic role of Glo2 in non-small-cell lung cancers, and this effect is mediated by a bioactive plant compound called Oleuropein. Another study from the same group revealed that Glo2 can be viewed as a driving force of prostate tumorigenesis and therefore, may represent a novel marker of progression in prostate cancer diagnosis [ 12 , 13 ]. It is a nice illustration, showing that Glo2 may have been overlooked in the context of malignancies and that there is still a lot of space for further studies.…”
Section: Introductionmentioning
confidence: 99%